1993
DOI: 10.1007/bf00006945
|View full text |Cite
|
Sign up to set email alerts
|

Opalinidae in African Anura. III. Genus Cepedea

Abstract: During 1988 and 1989, 409 specimens of southern African Anura comprising 50 species in 9 families were checked for opalinids in the cloaca. Cepedea acuta n. sp. was found in six of 19 Tomopterna cryptotis and four of seven T. krugerensis (Ranidae); C. affinis (Nazaretskaja, 1922) in two of four Afrixalus aureus, two of four Hyperolius horstocki, 23 of 42 H. marmoratus, one of seven H. pusillus, two of six H. semidiscus, and eight of 12 H. tuberilinguis (Hyperoliidae); C. magna Metcalf, 1923 in one of 20 Bufo g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…According to the form of the fixed cells and their size, these opalinids can be assigned to the species C. afiitzis as redescribed by Delvinquier et al (1993), and this is corroborated by the hosts in which we found them. The criteria used to characterize C. africana (Tuzet and Zuber-Vogeli 1954), C. crispata (Boisson 1965), and C. boissoni (Tuzet and Knoepffler 1968) are not sufficiently distinct to separate these species from C. aflinis; these species must be considered junior synonyms of C. affinis.…”
Section: Aflinitiesmentioning
confidence: 71%
See 3 more Smart Citations
“…According to the form of the fixed cells and their size, these opalinids can be assigned to the species C. afiitzis as redescribed by Delvinquier et al (1993), and this is corroborated by the hosts in which we found them. The criteria used to characterize C. africana (Tuzet and Zuber-Vogeli 1954), C. crispata (Boisson 1965), and C. boissoni (Tuzet and Knoepffler 1968) are not sufficiently distinct to separate these species from C. aflinis; these species must be considered junior synonyms of C. affinis.…”
Section: Aflinitiesmentioning
confidence: 71%
“…Cepedea affinis (Nazaretskaja, 1922) Delvinquier, Markus, andPassmore, 1993 Metcalf (1923) recorded this species from Heterixalus (formerly Megalixalus) madagascariensis. Later in the monograph, Metcalf (1923) recorded it from Hyperolius marmoratus, probably from East Africa, although the text indicates West Africa, where this frog species is not found (see Frost 1985;Passmore and Carruthers 1979;Schigtz 1975).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…In previous decades, extensive research around the globe led to the discovery and description of hundreds of opaline species, all of which are classified in five genera: Cepedea, Opalina, Protoopalina, Protozelleri ella, and Zelleriella (Delvinquier et al 1991a(Delvinquier et al , 1991b(Delvinquier et al , 1992(Delvinquier et al , 1995. The presence of only a few opalinid genera indicates that the level of morphological diversity at the genus level is low.…”
Section: Introductionmentioning
confidence: 99%